Change of Small Urban Centers in the Northern Corridor of Selangor From the Expansion of Klang-Langat Metropolitan Region Valley, Malaysia - Suhendro, Suhendro; Saleh, Yazid; Mahat, Hanifah; Hashim, Mohmadisa Hashim; Nayan, Nasir; Balkhis Norkhaidi, Saiyidatina; bin Ghazali, Mohamad Khairul Anuar (Sumatra Journal of Disaster, Geography and Geography Education, 2021)
This article aims to verify the critical elements in identifying factors for the change of small settlement centres due to overflow of the Klang-Langat Valley using the Exploration Factor Analysis (EFA) and Comfirmatory Factor Analysis (CFA) approach. This study involved 355 respondents from Hulu Selangor, Selangor selected by random sampling technique. The Likert scale questionnaires 1 until 5 were used to obtain feedback. Overall, the questionnaire reached the level of reliability with Alpha Cronbach value for each construct greater than 0.7. The collected data were processed through EFA for the grouping of the constructs and items for the change factor of small settlement centres. The CFA was done to verify the accumulated constructs based on their respective groups. The findings show that there are six constructs has been created which were access (5 items), environment (5 items), security (2 items), activity (4 items), neighbourhood (2 items) and infrastructure (2 items). Therefore, hopefully, the finding of this research can help in identifying factors to the transformation of small settlement centres due to the overflow of the Klang-Langat Valley and in the studies area in the transformation of small settlements. This is because the transformation driving a positive and negative impact on both urban and rural areas through increasing socioeconomic in society and ultimately contribute to the quality of life of the community in line with the current globalisation.